Experiences using SMART-system - Miyaji, C. (Sportinformatik gestern, heute morgen. Festschrift zu Ehren von Prof. Jürgen Perl, 2010)
SMART-system is a Video database, designed and developed at the Japanese In-stitute of Sport Science (JISS) to assist in the training activities of athletes and coaches. The purposes of the System are,